Impact of cognitive tasks on postural stability in young and older adults - Sakshi Shah; Nikita Nanavati (The Egyptian Journal of Otolaryngology)
Abstract Background Postural stability requires coordination of the visual, somatosensory, and vestibular systems. Cognitive tasks can divert attention from maintaining posture, potentially reducing body sway and fall risk. The effect on postural stability increases with cognitive load complexity. Understanding these aspects is crucial for studying the relationship between cognitive functions and postural stability, especially in older adults who may face declines in both areas. Method The study involved 70 participants, divided into 2 groups: group I consisted of 35 young adults, and group II included 35 older adults. Each participant underwent a hearing test using pure-tone audiometry and was screened for vestibular and cognitive function. Postural stability was assessed using a stabilometer, with evaluations conducted under various conditions, both with and without cognitive tasks. The cognitive tasks utilized included word generation, backward letter repetition, and backward serial 7 subtraction. Results Compared to noncognitive tasks, postural stability improved with cognitive tasks for both groups. When compared across different cognitive tasks, the backward letter repetition task enhanced postural stability more than word generation and backward serial 7 subtraction task. The most significant differences were observed on a cushioned surface with eyes closed when comparing noncognitive to cognitive tasks and across different cognitive tasks in both groups. However, younger adults exhibited better postural stability with cognitive tasks than older adults. Conclusion Postural stability was enhanced with cognitive tasks compared to noncognitive tasks for both young and older adults.